Generative Social Science : Studies in Agent-Based Computational Modeling - Epstein, Joshua M., 1951- (Book collections on Project MUSE., 2006)
Agent-based computational modeling is changing the face of social science. This book argues that this powerful technique permits the social sciences to meet an explanation, in which one 'grows' the phenomenon of interest in an artificial society of interacting agents: heterogeneous, boundedly rational actors.